2021
DOI: 10.1021/acs.iecr.0c05660
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Regulation Strategy of Solution-Mediated Polymorphic Transformation: A Case of 5-Nitrofurazone

Abstract: Solution-mediated polymorphic transformation (SMPT) exists extensively in crystallization from solution in many polymorphic systems. To obtain the desired products, it is crucial to understand the mechanism of the SMPT process and then to develop a regulation strategy for it. However, the mechanism of SMPT of different polymorphs is still not well understood. In this work, the mechanism and control strategy of SMPT were studied in detail by using 5nitrofurazone as a model compound. A series of SMPT experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It was observed that both the portion of water and the temperature of the SMPT experiments determined the results collected. A transformation from amorphous to other polymorphs or solvates by SMPT involves two processes, namely the dissolution of amorphous and the nucleation of the new solid-state phases. , Tables and indicate that as the water activity of MeOH/H 2 O and THF/H 2 O solutions increased and the temperature decreased, the solubility of nilotinib decreased consequently (the solubility curves and data could be found in Figures S7, S8 and Tables S14, S15, respectively) and became the rate-limiting step of the process, thus slowing down the transformation. In contrast, the decreased water activity would increase the solubility but inhibit the formation of hydrate form H3.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that both the portion of water and the temperature of the SMPT experiments determined the results collected. A transformation from amorphous to other polymorphs or solvates by SMPT involves two processes, namely the dissolution of amorphous and the nucleation of the new solid-state phases. , Tables and indicate that as the water activity of MeOH/H 2 O and THF/H 2 O solutions increased and the temperature decreased, the solubility of nilotinib decreased consequently (the solubility curves and data could be found in Figures S7, S8 and Tables S14, S15, respectively) and became the rate-limiting step of the process, thus slowing down the transformation. In contrast, the decreased water activity would increase the solubility but inhibit the formation of hydrate form H3.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of additives, only the β form was obtained in aqueous solution, while only the α form appeared under the action of the additives. Li et al 103 observed that adding a small amount of additive 5-nitrofurfural inhibited the generation of the α form of 5-nitrofurazone in acetonitrile solution, thus obtaining the γ form. Kwon et al 104 also found that the crystal form of polyene PyT1 changed in the presence of additive PyM1.…”
Section: Mechanisms Of Polymorphismmentioning
confidence: 99%
“…Therefore, the effects of TMAs on the stability of polymorphs can be evaluated by the lattice energy with incorporation of additives. 103,115 5.2. Investigation the Action Mechanism of TMAs.…”
Section: Prediction Of Conformationsmentioning
confidence: 99%
“…7−11 The occurrence of concomitant crystallization can significantly affect the consistency of the drug, leading to the reduction of bioavailability, dissolution performance, subsequent processing performance, and so on. 12,13 Therefore, the study of solution chemistry, molecular assembly, and its intrinsic connection with concomitant polymorphism are crucial in improving the quality of polymorphic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism is a common phenomenon in crystallization, especially in pharmaceuticals. The significant differences in performance between different polymorphs were brought to light by a number of drug withdrawals in the 20th century, and this is why the polymorphism in chemicals, especially in organic small molecule drugs, has gradually gained widespread recognition and attention in the last 30 years. Concomitant polymorphism is a special type, which refers to the phenomenon of simultaneous nucleation and growth of two or more polymorphs in the same environment under the combined influence of thermodynamic and kinetic factors. The occurrence of concomitant crystallization can significantly affect the consistency of the drug, leading to the reduction of bioavailability, dissolution performance, subsequent processing performance, and so on. , Therefore, the study of solution chemistry, molecular assembly, and its intrinsic connection with concomitant polymorphism are crucial in improving the quality of polymorphic outcomes.…”
Section: Introductionmentioning
confidence: 99%